Baking and Storage Stability of Retinyl Acetate (Vitamin A) Fortified Cookies - Mahmood, Shahid; Butt, Masood Sadiq; Anjum, Faqir Muhammad; Nawaz, Haq (Pakistan Journal of Nutrition, 2008)
Cookies were prepared from commercially available straight grade flour using Retinyl acetate (RA) as fortificant @ 30, 40 and 50% of Recommended Daily Allowance (RDA). The product was packed in Bioriented poly propylene (BOPP) and analyzed on monthly basis for physico-chemical and sensory attributes including baking and storage stability of the fortificant up to three month. The results revealed the non-significant influence of fortification on physico-chemical composition and sensory characteristics and the cookies containing 50% of RDA; Retinyl acetate were found the best in overall acceptability. Baking loss of Retinyl acetate was 9.30% while 8.33% loss was observed during storage.